A history of modern Brazil 1889-1964. Transl. from the Portuguese by J.L. Taylor. With a new concluding chapter by R.E. Poppino (Stanford University Press, 1966)
Orig. publ. in 1940. Orig. title: Historía da república (1889-1902).